Protein Hydrolysate Stimulates Growth in Tomato Coupled With N-Dependent Gene Expression Involved in N Assimilation - Sestili, Francesco; Rouphael, Youssef; Cardarelli, Mariateresa; Pucci, Anna; Bonini, Paolo; Canaguier, Renaud; Colla, Giuseppe (Frontiers in Plant Science, 2018)
Plant-derived protein hydrolysates (PHs) have received increased attention in the last decade because of their potential to improve yield, nutritional quality as well as tolerance to abiotic stressors. The current study investigated the effects and the molecular mechanisms of a legume-derived PH under optimal and sub-optimal nitrogen (N) concentrations (112 and 7 mg L-1, respectively) in tomato (Solanum lycopersicum L.). Growth and mineral composition of tomato plants treated with PHs by foliar spray or substrate drench were compared to untreated plants. In addition, the expression was determined of genes encoding ammonium and nitrate transporters and seven enzymes involved in N metabolism: nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase 1 (GS1), glutamine synthetase (2-GS2), ferrodoxin-dependent glutamate synthase (GLT), NADH-dependent glutamate synthase (GLS) and glutamate dehydrogenase (GDH). The root and total plant dry weight, SPAD index and leaf nitrogen content were higher by 21%, 17%, 7% and 6%, respectively in plants treated by a substrate drench in comparison to untreated tomato plants, whereas foliar application of PH gave intermediate values. PH-treated plants grown with lower N availability showed reduced expression of NR and NiR as well as of nitrate and ammonium transporter transcripts in both leaf and root tissues in comparison with untreated plants; this was especially pronounced after application of PH by substrate drench. Conversely, the transcript level of an amino acid transporter gene was up-regulated in comparison with untreated plants. At high N regime, the transcript levels of the ammonium and amino acid transporters and also NR, NiR and GLT were significantly up-regulated in root after PH foliar and substrate drench applications compared with untreated plants. An up-regulation was also observed for GS1, GS2, and GDH transcripts in leaf after substrate drench. These results highlighted the potential benefits of using legume PH in vegetable production systems to increase growth and N-nutritional status of plants.